O reconhecimento em Medeia, de Eurípides, e em Anjo Negro, de Nelson Rodrigues - Etiene Martins Lage Duarte (2024)
This dissertation intends to discuss the relevance of recognition (anagnórisis), a constituent element in tragedies, listed by Aristotle, in Poetics, as a thematic axis that will allow establishing parameters for defining the dramatic/literary genre “tragedy”. Using this tool, the works Medea, by Euripides (431 BC) and Anjo Negro, by Nelson Rodrigues (1948), will be analyzed, considering their proximity or distance from classical Greek tragedy. The investigation of Aristotelian recognition, therefore, will be the leitmotif that will allow us to compare these two works from such different historical contexts and from different nationalities. Furthermore, the perception of recognition addressed in this work will focus mainly on the role of memory as a process of identity/recognition in the two works that used the myth of Medea. Thus, we have sought to detect, evaluate and catalog the occurrences and functions of recognition in the selected Medeas. It was established in the analysis of this dissertation that the Euripidean Medea is an inhuman, divine being. Therefore, this factor corroborates the conclusion that there is no way to state that there was, in fact, recognition, effected by memory, in Aristotelian terms in tragedy. Although it was possible to perceive a movement of the character that may resemble self-recognition, through the rescue of the past (memory). The play Anjo Negro, built within the parameters of the “Rodriguese tragedy”, addresses characters who do not have any divine traits or antecedents. Virginia, here considered Nelson Rodrigues' Medea, is a human character and, therefore, has actions that correspond to the human sphere, even though throughout the play there are circumstances that border on dehumanization. The choir's final speech in the play, as well as the initial one, appears prophetic like the Greek chorus: it announces that the murders of Virginia's children will be repeated, she will become pregnant, through Ismael's rape, and will murder her offspring. There was no proof in the play that the recognition awakened by memory on the part of the character occurred. In this way, it will be demonstrated that the memories of Virgínia and Ismael, evoked throughout the play, highlight the crimes and errors committed by the characters in the play. What can be concluded, with the act of filicide as a common denominator between the characters Medea and Virgínia, is that their actions are perpetrated above good and evil. Both do not recognize what they do as a crime, while Medea acts as a goddess or monster, Virginia, even represented as human, like Ishmael, acts excessively. Thus, the recognition woven by memory on the part of the characters was not detected in the investigation of the Euripidean tragedy and in Anjo Negro. However, it can be seen that Euripides, in 431 BC, ends Medea in a lacunar way, leaving the judgment of the characters in the hands of reception. Nelson Rodrigues, in Anjo Negro, reveals the most hidden vices and misfortunes, through the characters' characters and the environment that confines them, ending the play with the prophetic chorus that announces the repetition of the cycle of misfortunes. In this way, the playwright casts the role of judging the characters' actions to the audience.